New combined heat transfer enhancement techniques used in laminar flow through non-circular ducts. (25th December 2019) - Ranjan, Hrishiraj; Bharti, Anand Kumar; Emani, Madhu Sruthi; Meyer, Josua Petrus; Saha, Sujoy Kumar
Highlights: Laminar flow through non-circular ducts with inserts is studied experimentally. Uniform wall heat flux boundary condition is imposed on the channel outer wall. Wide Prandtl number range is covered using viscous Servotherm medium oil. Heat transfer and pressure drop characteristics against Reynolds number are plotted. Correlations developed and performance evaluation is done and these are beneficial. Abstract: The problem of heat transfer enhancement using different combinations of transverse ribs, transverse corrugations and twisted-tape insert with oblique teeth, twisted tape with centre clearance and helical screw-tape insert in square and rectangular channel was investigated. The study also involved the thermohydraulic performance of inserts in non-circular channels in the laminar regime. Non-circular channels having aspect ratios of 1, 0.5 and 0.33 were considered. The techniques used for heat transfer augmentation in the present study were and the problem was (1) transverse ribs with twisted tape with oblique teeth, (2) integral transverse corrugation and centre-cleared twisted-tape insert, (3) transverse rib and helical screw-tape insert, (4) axial ribs and centre-cleared twisted-tape insert and (5) integral transverse rib and centre-cleared twisted-tape insert. These combined fin geometry are supposedly important from possible heat transfer enhancement point of view. In the channels, the combined influence of insert geometry such as rib pitch, rib height, twist ratio of twisted tape, twisted tape tooth horizontal length and twisted tape tooth angle was studied. The experiment was carried out using Servotherm oil as the working fluid, which had a wide range of Prandtl number (430–530). Uniform heat flux boundary condition was used. The methods used in the experiment have been discussed in the text of the presentation. The important results of the experimental investigation showed that the thermohydraulic performance using a combination of inserts was better than that of bare ducts and that of the individual enhancement technique acting alone. Both the increase in pressure drop and heat transfer augmentation occurred due to the addition of inserts, but heat transfer enhancement dominated over the increase in pressure drop. Nusselt number and friction factor correlations have also been developed and are presented in this paper. The experimental program considered different fin arrangements with various parameters and therefore, it should be very helpful in designing heat exchangers of different shapes and sizes used for industrial purpose. It is concluded from the present investigation that 31–52 per cent increase in heat duty at constant pumping power and 25–36 per cent reduction in pumping power at constant heat duty are achievable. This is the novelty of the present work since no such study and the observations have been made earlier. These types of combined fin configurations have not been tried before. The findings are likely to have good impact in the industry.